ANALISIS MISKONSEPSI IPAS MATERI WUJUD ZAT DAN PERUBAHANNYA MELALUI TWO-TIER MULTIPLE CHOICE (TTMC) KELAS IV SD - Frida Ashofa; Diana Endah Handayani; Singgih Adhi Prasetyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the high number of students who hold misconceptions about the concept of the states of matter and their changes, which has become the main focus of this study. These misconceptions are caused by limited use of instructional models, lack of interactive media, and students’ low self-confidence and reading ability. The purpose of this study is to analyze students' misconceptions in the IPAS subject related to the states of matter and their changes in Grade IV of elementary school. This research employed a descriptive qualitative approach, using data collection techniques such as interviews, observations, written tests, and documentation. The subjects of the study were Grade IV elementary school students. The instrument used was a Two-Tier Multiple Choice (TTMC) test. The results showed that 21% of students experienced misconceptions, 45.7% did not understand the concepts, 18.3% had alternative conceptions, and only 15% truly understood the concepts. Most misconceptions were found in the subtopics of heat absorption and release, phenomena of changes in states of matter, types of phase changes, the concept of states of matter, and the properties of matter. Students were generally able to answer correctly but provided reasoning that was not scientifically accurate. These findings indicate that the level of students' misconceptions regarding the states of matter and their changes remains relatively high.